Whole-plant grain sorghum silages for growing cattle - R. Smith; K. Bolsen; J. Hoover (Kansas Agricultural Experiment Station Research Reports, 1986)
Four trails were conducted to determine the effects of processing (rolling before feeding, with rolls set to break 95% of the kernels) and stage of maturity at harvest on the nutritive value of whole-crop grain sorghum silages for growing cattle. Rolling mid-dough silages did not improve feeding value. However, rolling at later maturity stages increased cattle gains and feed efficiencies, with the more mature, hard-grain silages giving the greatest response. Only starch digestibility was consistently affected (increased) by processing. Silage dry matter (DM) intake tended to increase, but feed efficiencies tended to decrease with advancing maturity. Neither average daily gains nor DM digestibilities were affected by stage of maturity at harvest. However, starch and crude protein (CP) digestibilities were highest for the late-dough silage in one trial and for the early-dough silage in another. Dry matter content and DM recovery from the silos increased and silage CP content decreased with advancing maturity.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Grain sorghum silage; Growing cattle